1999
DOI: 10.1292/jvms.61.343
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Metallothioneins-I & -II and -III in the Brain of Aged Dog.

Abstract: ABSTRACT. Localization of metallothionein (MT) -I & -II and MT-III and its significance in the brain aging in dogs were examined using immunohistological and molecular pathological techniques. MT-I & -II immunohistochemistry showed positive staining in the hypertrophic astrocytes throughout the aged dog brains; these MT-I & -II immunoreactive astrocytes were predominant in the cerebral cortex and around the blood vessels in the brain. These findings dominated in the brain regions with severe age-related morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In the CNS, MT-I/II is expressed at relatively low levels during fetal development and increases significantly after birth as has been characterised in the developing brain of sheep (Chung et al, 2002b). Further, Kojima et al (1999) reported that in the aged brain of the dog MTs I and II were localized to the astrocytes of the cerebral cortex and around the blood vessels where severe age-related morphological changes were observed. For example, Suzuki et al (1994) showed that ageing is a significant inducer of MT-I/II, and a notable difference was seen in the aged brain when compared to the young brain; while Natale and colleagues observed MT-I/II to increase in the mouse brain over development to maturity (Natale et al, 2004).…”
Section: Metallothionein Expression In the Ageing Brainmentioning
confidence: 87%
“…In the CNS, MT-I/II is expressed at relatively low levels during fetal development and increases significantly after birth as has been characterised in the developing brain of sheep (Chung et al, 2002b). Further, Kojima et al (1999) reported that in the aged brain of the dog MTs I and II were localized to the astrocytes of the cerebral cortex and around the blood vessels where severe age-related morphological changes were observed. For example, Suzuki et al (1994) showed that ageing is a significant inducer of MT-I/II, and a notable difference was seen in the aged brain when compared to the young brain; while Natale and colleagues observed MT-I/II to increase in the mouse brain over development to maturity (Natale et al, 2004).…”
Section: Metallothionein Expression In the Ageing Brainmentioning
confidence: 87%
“…This is consistent with the results of studies of metallic Hg exposure (Yoshida et al 2004, 2005); a lower brain Hg concentration may not guarantee lower toxicity, supporting the protective role of the protein. Earlier studies suggest that brain MT-I,II has an important role both in the response to oxidative injury (Potter et al 2007) and in the process of aging (Kojima et al 1999). Therefore, the lack of MT can exaggerate the toxicity of MeHg by enhancing the initial effects due to oxygen radicals and/or by accelerating functional aging.…”
Section: Discussionmentioning
confidence: 99%
“…However, many other reports have not supported an astrocyte-specific MT-3 expression. Although in most cases no thorough cell identification has been established by robust methods such as double labeling or use of the MT-3 KO mice as controls, in the normal brain it appears that the MT-3 mRNA signal is more consistent with neuronal than with glial cells, with astrocyte MT-3 upregulation eventually occurring following injury (26,27,36,53,(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68). In contrast to the MT-3 messenger, the MT-3 protein has been shown to be present mainly in astrocytes by a number of studies (36,40,65,66,(69)(70)(71)(72)(73)(74).…”
Section: Expression Of Metallothionein-3 In the Central Nervous Systemmentioning
confidence: 99%
“…In contrast to the MT-3 messenger, the MT-3 protein has been shown to be present mainly in astrocytes by a number of studies (36,40,65,66,(69)(70)(71)(72)(73)(74). Other reports, however, show MT-3 protein presence basically in neurons (63,64,(75)(76)(77). One report demonstrated MT-3 protein not only in neurons, astrocytes and microglia, but also in oligodendrocytes, following lipopolysaccharide (LPS) injection (78).…”
Section: Expression Of Metallothionein-3 In the Central Nervous Systemmentioning
confidence: 99%